RICARDO, Antunes L. O caracol e sua concha: ensaios sobre a nova morfologia do trabalho, São Paulo: Boitempo, 2005. - Mariano, Cláudia Aparecida Moraes (Universidade Estadual de Campinas, 2012)
Resenha